Avaliação das práticas de participação da Gestão Colegiada nas Escolas Públicas Estaduais do Ceará. - Oliveira, Ivan de (2006)
The basic question directing this research was: How do the public schools at primary and secondary levels in the State of Ceará that have the Development School Plan (DSP) respond to a constitutional demand that the principal of Democratic Management be applied in all public schools. The inclusion of democratic management in the Federal Constitution of 1988 was something rather new as no other federal document had included it. The study tried to verify the existence of effective collegiate participation in school management in the public state schools of Ceará. It also tried to discover what level of relationship existed between these same schools and other departments in the State Secretariat of Education (SEDUC) and the regional centers for educational development (CREDE). The research was carried out through non structural interviews with representative members of school councils in 82 of the state schools. Personal observation of the manner in which these councils met and functioned was also carried out. The interpretation and explanation of what was discovered was based strictly on the principles of hermeneutic phenomenology. Seven distinct categories were presented as concrete expressions of democratic school participation: the notion of participation, the participation of different segments of the school and local communities, the decisions made at council meetings, the number of meetings held, the difficulties involved in participation for various segments of school management, the organizations present in the school management, and the relationship between the school, CREDE an SEDUC. We concluded that contrary to what was idealized the working together of members of school management and local communities, the mechanism used the system simply did not work.